The study of Quranic teaching and learning: United Kingdom experience - Che Noh, Mohd Aderi; Tamuri, Ab. Halim; Abd. Razak, Khadijah; Suhid, Asmawati (Mediterranean Center of Social and Educational Research, 2014)
Al-Quran is the revelation to Prophet Muhammad (PBUH) started with the word “Iqra’’. Prophet (PBUH) had implemented five principles of al-Quran teaching and learning which his companions and the next generation follow until today. The model consist of Tilawah (good and fluency recitation), Tafahum and Tafsir (knowing and understanding the meaning), Tatbiq (appreciate and implantation of the teaching in daily life), Tahfiz (memorizing some verses for practice and reciting during prayer) and Taranum (reciting al-Quran with a good voice and proper song). In this part of the article, the main areas of discussion will be how the Qur’an is taught in the Muslim community in particular in their mosques, madrasas and community centres and hence their method of teaching and then how it is perceived by the audience i.e. the students, teachers and also parents. The study found that the teachers have been using a variety of strategies in implementing quranic teaching and learning, some teaching methods such as conventional and others reflect new methods taking into consideration the different abilities of the children. This style of teaching totally ignores the quality of recitation and teaching with the rules of Tajwid. This article will then lead to a conclusion, which will include some suggestions on how to improve the main curriculum and how the Qur’an should be taught.